2016
DOI: 10.1111/jog.13096
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in liver transplant recipients: A 15‐year single‐center experience

Abstract: Pregnancy after liver transplantation can achieve relatively favorable outcomes. Obstetricians should be involved in the contraceptive and fertility counseling of female transplant recipients to prevent unintended pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The number of pregnancies in LT recipients has been rising steadily over the last few decades. Pregnancy outcomes in a meta‐analysis and a number of case series, including our own unit, are favorable, but inherent fetal and maternal risks remain . These women will expect and require extensive counseling regarding contraception and pregnancy from their transplant physicians and obstetrics team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of pregnancies in LT recipients has been rising steadily over the last few decades. Pregnancy outcomes in a meta‐analysis and a number of case series, including our own unit, are favorable, but inherent fetal and maternal risks remain . These women will expect and require extensive counseling regarding contraception and pregnancy from their transplant physicians and obstetrics team.…”
Section: Discussionmentioning
confidence: 99%
“…For young women, there is an expectation of returning to a normal quality of life after LT, including the ability to have children . Pregnancy outcomes following LT including previous reports from our own center have been shown to be favorable, but with an increased risk of premature birth, intrauterine growth restriction, and graft dysfunction . The dominant prepregnancy advice was to recommend deferral of pregnancy to a time period >1 year following transplant.…”
mentioning
confidence: 99%
“…Rates of pre‐eclampsia in the general US population have previously been reported as 4% . Older studies in pregnant LT recipients have reported pre‐eclampsia rates of 21%‐26%, whereas newer studies have reported rates of 7%‐12% . Rates may have improved over time as a result of better management of immunosuppression and risk factors (Table ) associated with pre‐eclampsia.…”
Section: Maternal Outcomesmentioning
confidence: 99%
“…Rates of graft rejection in pregnant LT recipients can be highly variable between 0% and 20% . Unfortunately, some of these studies did not employ uniform diagnostic criteria for ACR.…”
Section: Maternal Outcomesmentioning
confidence: 99%
“…However, it only takes a quick literature search to heighten concern. Case reports describe rejection and graft failure, pre‐eclampsia, fetal demise, maternal demise, and fetal anomalies . Unfortunately, the information available during prepregnancy counseling allows little predictive ability.…”
mentioning
confidence: 99%